Social support and religion. Protective factors of symptoms of depression throughout the complex Haitian migration trajectories in Santiago (Chile) and Tijuana (Mexico) - Hogan, Annika; Espinoza-Ortiz, Ana Karen; Díaz-Valdes, Antonia; Sisay, Emnet; Rocha-Jiménez, Teresita (Revista Chilena de Antropología, 2024)
As complex migration trajectories become increasingly more common, understanding potential protective factors of symptoms of depression is critical. Therefore, the aim of this paper was to understand how social support and religion may be associated with better outcomes for migrants’ mental health among Haitian migrants at different points in their intricate migration trajectories. Through a quantitative cross-sectional study using a non-probabilistic sampling, we surveyed 405 Haitian migrants in Santiago, Chile (n=207), and Tijuana, Mexico (n=198). Bivariate analyses revealed that participants in Chile had a longer time post-migration (4.6 years) than those in Mexico (3.7 months) (Chi-square p<0.001). Multivariable logistic regression findings confirm social support and religion are protective factors of depression symptoms but differ depending on the point in the migration trajectory. Having someone to trust was a significant protective factor for Haitian migrants in Chile (OR= 0.187, 95% CI 0.054 – 0.646, p=0.008) and Mexico (OR=0.080, 95% CI 0.007 – 0.858, p=0.037). Identifying with a religion reduced the odds of depressive symptoms by 60.3% for those in Chile (95% CI 0.170 – 0.923, p=0.032) but not in Mexico. Findings support re-classifying protective factors such as social support as dynamic, highlighting experiences in each migration step, rather than linear or non-static. Findings provide insight into how to best prevent and treat mental health throughout migrants’ diverse journeys. Ideally, future longitudinal studies should explore the nuances of social support during different migration phases in Latin America and their relation to mental health outcomes.